Slab models beneath central Myanmar revealed by a joint inversion of regional and teleseismic traveltime data - Yao, Jiayuan (2021)
The intermediate-depth (50–180 km) seismicity beneath Myanmar provides direct evidence of the subducting Indian slab. However, the historic lack of regional seismic observations leads to previous low-resolution models that show large variations in slab geometry beneath Myanmar. The depth extent and morphology of the slab are still poorly known. In this study, we conduct a joint inversion of regional and teleseismic P-wave traveltimes from recently installed networks to image seismic velocity structures beneath central Myanmar by adopting an eikonal equation-based traveltime tomography method. The observations contain a total of 6,069 regional first P-wave arrivals and 29,787 teleseismic P-wave differential traveltimes. We find a high P-wave velocity anomaly beneath central Myanmar, which starts from ∼50 km depth and extends continuously to the mantle transition zone (MTZ) and is interpreted as the subducting Indian slab. Below 100 km depth, the dip angle of the slab in the south is ∼15° larger than that of the slab in the north, suggesting a possible slab tearing. Based on our tomographic results and previous studies, the slab in the north is inferred to have a deep stagnant segment lying above the 660-km discontinuity in the MTZ, but whether it is connected with the shallow dipping slab cannot be confirmed. Meanwhile, the slab in the south may just stay in the upper mantle (above 410 km), but it may also have penetrated the 410-km discontinuity. Taking into account all the scenarios, we propose four possible models of the Indian Plate subduction system beneath central Myanmar.